Edukasi Terapi Komplementer dengan Terapi Herbal Kunyit Asam dan Buah Nanas untuk Mengatasi Dismenorea Primer - Safitri, Safitri; Hayati, Fatihatul (Jurnal Abdimas Kesehatan (JAK), 2025)
Adolescence is a period of physical and secondary sexual growth changes, one of which is menstruation. Primary dysmenorrhea is an uncomfortable sensation centered in the lower abdomen. The prevalence of dysmenorrhea in Indonesia reaches 98.8% in adolescents. Menstrual pain has a direct effect that negatively impacts the quality of life of adolescents, such as disrupting physical activity and even causing adolescents to miss school. Complementary therapy is one of the therapies to overcome primary dysmenorrhea, including herbal therapy. Turmeric tamarind and pineapple have been proven effective and easily available around the residence to overcome primary dysmenorrhea. The results of an initial survey at SMA N 7 Jambi City obtained information that the experience of adolescent girls in overcoming primary dysmenorrhea was only by resting or sleeping while rubbing eucalyptus oil and drinking warm water, as well as the lack of information from health workers regarding complementary therapy with herbal therapy of turmeric tamarind and pineapple to overcome primary dysmenorrhea. The purpose of this community service activity is to provide education and early treatment to adolescent girls who experience primary dysmenorrhea. The implementation of the activity was in the form of providing education about complementary therapy with turmeric tamarind and pineapple to overcome dysmenorrhea. This community service activity was carried out on 22 adolescents in class XII F1 at SMAN 7 Jambi City in July 2024. The expected output target is an increase in knowledge between before and after being given education. The method used is education using leaflets. Knowledge is assessed through the results of filling out the questionnaire. Monitoring and evaluation of activities with a one group pretest and posttest design approach. The results of the community service showed an increase in knowledge after being given education on the use of complementary therapy to overcome dysmenorrhea by 54.5%, expected adolescents girls can use herbal therapy of turmeric tamarind and pineapple as an alternative to overcome dysmenorrhea independently.